Cyclic behaviour of CFRP confined concrete under axial compression. (18th July 2022) - Adafer, S.; Si Youcef, Y.; Amziane, S.
Highlights: The cyclic behaviour of CFRP confined concrete columns under compressive loading is investigated. The effect of varying the confinement rate on the cyclic characteristics is analysed. The effect of the specimen shape on the cyclic behaviour of the confined concrete is examined. CFRP envelopes attenuated the degradation of all the reinforced specimens. Independence of the plastic strain and the stiffness degradation from the confinement rate is shown. Abstract: This research aims to experimentally investigate the cyclic behaviour of externally strengthened concrete with carbon fibre reinforced polymer composites (CFRP). This paper presents the results of monotonic cyclic compression tests conducted on 17 specimens – 9 cylindrical and 8 prismatic – with identical slenderness ratios of 2. The transverse cross-sectional shape and the confinement rate were the main test variables. The experimental results are presented as axial stress-axial strain cyclic responses. When compared to existing results in the literature, the envelope curves obtained show almost identical behaviours, confirming that confinement has a positive effect on strength and deformability. Such confinement is more effective in cylindrical specimens than prismatic ones. After analysing of the cyclic responses, the influence of varying the confinement rate on the cyclic parameters was investigated. Polynomial correlations of the secant stiffness and the plastic strain as a function of axial strain were highlighted. The results show that for both geometric shapes, the residual strain and stiffness degradation are independent of the confinement rate. Contrarily to the dissipated and restored energies, which are significantly affected by increasing number of CFRP layers. The results also indicate that the variation of the dissipated energy, restored energy and damage capacity consists of two successive phases; the first corresponds to the pre-peak phase where the responses are almost confused, followed by a second phase which corresponds to the post-peak phase where the responses are dispersed.